Estimating the magnitude of clinical benefit of systemic therapy in patients with DCIS or pre-invasive disease of the breast. (November 2019) - Lazzeroni, Matteo; Puntoni, Matteo; Provinciali, Nicoletta; Webber, Tania Buttiron; Briata, Irene Maria; D'Amico, Mauro; Giuliano, Silvia; Siri, Giacomo; Cagnacci, Sara; DeCensi, Andrea
Abstract: The challenge of effective management of ductal carcinoma in situ (DCIS) and other pre-malignant disorders of the breast is to select patients who will not progress to invasive carcinoma from those at the highest risk who require radiotherapy and/or endocrine therapy to minimize the risk of a subsequent invasive recurrence. Although IBIS-II and NSABP-B35 DCIS phase III trials proved that tamoxifen 20 mg/day and anastrozole reduce the risk of ipsilateral and contralateral events, the toxicities of both drugs have hampered the drug uptake by high-risk women. We recently reported results of a 3-year placebo-controlled trial of low-dose (5 mg/d) tamoxifen in 500 women with intraepithelial neoplasia (70% DCIS). At a median follow-up of 5 years, women randomly assigned to low-dose tamoxifen had half the number of subsequent diagnoses of DCIS or invasive cancer compared with those randomly assigned to placebo but no increase in thromboembolic events or endometrial cancers. The 5-year number needed to treat was 22 (95% CI, 20–27). Our attention is now focused on prognostic and predictive markers to identify patients who can derive the greatest benefits from low dose tamoxifen, such as for instance the expression of 23 genes involved in cell cycle progression (CCP). In conclusion, we endorse an active treatment of DCIS as the standard of care.